Phytochemical studies and medicinal properties of cinnamomum zeylanicum / Nurasyikin Basir - Basir, Nurasyikin (Faculty of Applied Sciences, 2017)
Phytochemical screening, antioxidant and antibacterial activities on stem bark of Cinnamomum zeylanicum has been studied. Cold extraction process was carried out using three different polarity of solvent which are hexane, chloroform and methanol. Methanol crude extract gives the highest percentage of yield compared to others which is 14.38%. Phytochemical screening shows the presence of many active compounds in methanol crude extract of C. zeylanicum in the form of secondary metabolites which are alkaloid, flavonoid, tannin, glycoside, steroid, quinone, saponin, sterol, phenol and terpenoid. All crude extracts of C. zeylanicum significantly inhibited the growth of the pathogenic bacteria such as Bacillus subtilis, Staphylococcus aureus, Salmonella typhi and Escherichia coli. Chloroform crude extract revealed the highest diameter of inhibition zone against pathogenic bacteria which is 23 mm to 52 mm. Moreover, thin layer chromatography (TLC) shown better separation in solvent system with ratio 1 :9 of chloroform:hexane in hexane crude extract while 9: 1 of chloroform:toluene in chloroform crude extract. Furthermore, all the crude extracts shown positive result in antioxidant activity using thin layer chromatography (TLC) bioautography.